Implementasi Konsep Therapeutic Space pada Strategi Desain Pusat Rehabilitasi Penderita Depresi - Amelia Fitri Kusumawardani; Sri Yuliani; Ofita Purwani; Meliana Yustika Santi (Universitas Sebelas Maret Surakarta, 2022)
The therapeutic space approach is an architectural concept that emphasizes the interaction of psychological and physiological elements in order to improve the well-being of patients through utilizing the functions of the built environment. It is necessary to further research into the connection between depression and the concept of therapeutic space is required. Therefore, this research identified the needs of people suffering from depression related to therapeutic space. Method used analysis content of three theories and comparative content of them. The of therapeutic space theories are compared consist of Chrysikou, Jordan, and Liddicoat. The results of the comparison of the three theories are modified as the guidelines theory suitable for considering in designing of therapeutic space in the rehabilitation center for depression disorder by integrated harmony with nature.